DETERMINAN LOYALITAS PELANGGAN, STUDI EMPIRIS PADA MIKIE HOLIDAY & RESORT BERASTAGI - JURNAL DARMA AGUNG LPPM; Ronnie MT Sirait (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
The purpose of this study was to analyze the influence of image, price, and trust on customer loyalty either partially or simultaneously. This research is a quantitative description with an opinion gathering instrument with a questionnaire. The sample in this study were 22 people. Technique of analysis uses multiple linear regression. Primary data were processed with SPSS. Research resulted multiple linear regression equation, namely Y = 8,094 + 0,212X1 + 0,706X2 + 0,466X3. Hypothesis test resulted: Image partially affects customer loyalty, price partially affects customer loyalty and trust partially affects customer loyalty. Furthermore. There is a significant influence simultaneously on image, price and trust on customer loyalty. Adjusted RSquare is 0.746, meaning that the research variable has a significant contribution in explaining customer loyalty, which is 74.60%, while the remaining 25.40% is explained by other factors